2018
DOI: 10.1016/j.chom.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Modulated Metabolic Reprogramming Is Required for DUOX-Dependent Gut Immunity in Drosophila

Abstract: DUOX, a member of the NADPH oxidase family, acts as the first line of defense against enteric pathogens by producing microbicidal reactive oxygen species. DUOX is activated upon enteric infection, but the mechanisms regulating DUOX activity remain incompletely understood. Using Drosophila genetic tools, we show that enteric infection results in "pro-catabolic" signaling that initiates metabolic reprogramming of enterocytes toward lipid catabolism, which ultimately governs DUOX homeostasis. Infection induces si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 63 publications
4
95
0
Order By: Relevance
“…This is consistent with previous results showing that intestinal barrier failure after loss of a septate junction protein Snakeskin (Ssk) results in altered gut morphology, dysbiosis, and reduced Duox level (37). Duox act as an important defense mechanism in ECs against enteric infection and its expression is increased in the intestine upon infection and aging (20,55), while its expression is dampened in the tumor-bearing intestine with massive loss of ECs and impaired EC renewal capacity. A recent study demonstrated lactic acid from L. plantarum activates Nox for ROS production that promotes intestinal damage and dysplasia (21).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous results showing that intestinal barrier failure after loss of a septate junction protein Snakeskin (Ssk) results in altered gut morphology, dysbiosis, and reduced Duox level (37). Duox act as an important defense mechanism in ECs against enteric infection and its expression is increased in the intestine upon infection and aging (20,55), while its expression is dampened in the tumor-bearing intestine with massive loss of ECs and impaired EC renewal capacity. A recent study demonstrated lactic acid from L. plantarum activates Nox for ROS production that promotes intestinal damage and dysplasia (21).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous results showing that intestinal barrier failure after loss of a septate junction protein Snakeskin results in altered gut morphology, dysbiosis and reduced Duox level (Salazar et al, 2018). Duox act as an important defence mechanism in ECs against enteric infection and its expression is increased in the intestine during infection and ageing (Lee et al, 2018;Guo et al, 2014), suggesting that Duox expression is induced during normal intestinal regeneration under infection or ageing, while its expression is dampened in the tumor bearing intestine with massive loss of ECs and impaired EC renewal capacity. A recent study demonstrated lactic acid from L. plantarum activates Nox for ROS production that promotes intestinal damage and dysplasia (Iatsenko et al, 2018).…”
Section: Tumor Growth Causes Intestinal Dysfunction and Dysbiosissupporting
confidence: 93%
“…from mothers to offspring) (Bakula 1969; Starmer et al 1988; Spencer 1992; Ridley et al 2012; Wong et al 2015; Téfit et al 2018). Second, host immune system participates to the destruction of harmful gut bacteria and the retention of beneficial ones (Lee et al 2017; Lee et al 2018). Third, Drosophila larvae actively search and associate with beneficial yeast species ensuring they engage in symbiosis with locally adequate nutritional symbionts (Fogleman et al 1981; Fogleman et al 1982).…”
Section: Discussionmentioning
confidence: 99%